A review of best international life cycle assessment (LCA) practices in wood construction: Challenges for Ireland - Song Ge; Conan O'Ceallaigh; Patrick J. McGetrick (Cleaner Environmental Systems)
Under the dual pressure of carbon-neutral commitments by 2050 and increasing housing demands, the Irish construction industry is responsible for a 50% reduction in carbon emissions relative to 2018 levels. Timber has been identified as an excellent material choice for embodied carbon reduction. However, the widespread adoption of timber in construction is limited by several factors, including established practices and supply chains, and lack of public policy and incentives to quantify and reduce embodied carbon. The latter needs to be supported by accurate quantitative life cycle assessment (LCA). To identify gaps and challenges faced by LCA development for timber construction, this paper reviews various up-to-date Irish and international LCA practices. At the product level, 26 environmental product declaration (EPD) databases and 35 EPDs covering five wood product types are analysed. At the building level, 29 national and international building LCA methodologies worldwide are compared. Due to varying availability of Irish-customised data, disparities exist between the lifecycle inventory data used in current Irish timber product EPDs and other Irish-focused statistics. The challenges identified include a lack of mandatory regulations on embodied carbon disclosure and thresholds, a limited number of wood product EPDs in Ireland, and incomplete lifecycle inventory data.